Status of the oral component of health in the Argentine Republic. Pre pandemic report - Pistochini, Adriana (2020)
The purpose of this article is to analyze part of the oral health situation in Argentina. A decentralized federal state, made up of twenty-four jurisdictions with political autonomy, twenty-three provinces, and an autonomous city. Dental caries affects more than half of the population and is the most common pathology in school-age children. The average DMFT at 12 years is 5.11. Every year 3000 new cases of oral cancer are confirmed. The National Directorate of Bucodental Health is recognized as the rector of the actions related to the oral health component and implements the following programs: National Oral Cancer Program, National Oral Rehabilitation Program and Prevention and Primary Oral Assistance Program. Focused on strengthening the first level of care with a model of resolute capacity with transdisciplinary teams, developing a monitoring system and unifying the dental clinical record with the consent of the patient.